LYDGATE AND HUMANIST READING: AUGUSTINE'S CONFESSIONS, PETRARCH'S SECRETUM, AND LYDGATE'S 'TESTAMENT'. - SWEET, W. H. E. (Medium Aevum, 2023)
The article focuses on John Lydgate's exploration of humanist reading through his late autobiographical poem 'The Testament of Dan John Lydgate'. Topics include Lydgate's engagement with Augustine's Confessions and Petrarch's Secretum, the structure of the 'Testament' in five sections, and Lydgate's evolving justification of humanist reading in the context of contemporary attitudes.